Liposomal drug release using ultrasound and modeling release dynamics for model predictive controller design - Moussa, Hesham Gamal (2015)
A Master of Science thesis in Electrical Engineering by Hesham Gamal Moussa entitled, "Liposomal drug release using ultrasound and modeling release dynamics for model predictive controller design," submitted in June 2015. Thesis advisors are Dr. Nasser Qaddoumi and Dr. Ghaleb Husseini. Soft and hard copy available.